Antecedents And Outcomes Of Social Enterprises Resilience In Bangladesh - Afrin, Samina (2025)
This research aims to explore the antecedents and outcomes of social enterprises resilience in bangladesh. Understanding the hybrid nature and resource limitations of social enterprises, this study seeks to understand the effect of different dimensions of social capital and social network ties on social enterprises resilience under the mediating role of innovativeness. The concept of resilience at organizational level refers to the ability of a firm to survive disruptions and catastrophic events in the face of substantial changes in the business and economic environment. There is a growing stream of literature in the field of social enterprise focusing on the challenges arising from social enterprises’ hybrid structure of social and economic missions, and social enterprises’ management and performance under disruptive conditions. This research builds on this perspective and draws insights from the organizational resilience literature to address the knowledge gap in social enterprises’ resources and capabilities and innovative activities regarding their resilience capability and social and economic performance. Considering the effect of resources (social capital, social network, innovativeness) on capabilities (organizational resilience), a theoretical framework has been developed based on resource based-view (rbv) perspective. On the other hand, social capital theory has been applied to explain the different dimensions of social capital.